ON THE ISSUE OF IMPLEMENTATION OF INTERNATIONAL EXPERIENCE IN FINANCIAL ASSETS REGULATION: CRYPTOCURRENCIES - LIUBKINA, Olena; TKACHENKO, Oleksandr (Scientific journal «World of Finance», 2021)
Introduction. The digitalization of the economy is closely linked to the formation of an effective legal framework. Any development or operation of digital instruments must be accompanied by appropriate financial and legal regulation. The study of the functioning of digital financial assets allowed us to conclude that, unfortunately, their rapid development is observed against the background of the lag of regulatory regulation of the relevant legal relations that are formed as a result of such activities. A critical scientific analysis of international experience in the field of financial regulation of cryptocurrencies has identified a number of key generalizations. The purpose of the article is to identify the main markers of digital financial assets, study international experience in financial regulation of virtual assets, including cryptocurrencies, identify opportunities to implement positive foreign practices to Ukrainian realities and diagnose the current state and prospects of cryptocurrency in Ukraine. Results. The specific characteristics of digital financial assets are substantiated, namely: freedom of issue, availability of cryptocurrencies, absence of intermediaries, high degree of protection, openness to developers, integration with the latest technologies that produce new digital products. The international practice of state regulation of cryptocurrencies is generalized in terms of both the interpretation of the conceptual apparatus and in view of the qualification of the mechanism of conducting operations with digital assets. It is proved that in Ukraine from the point of view of legal regulation of cryptocurrency is still outside the full framework of the legal field of domestic legislation. The main innovations and specifics of regulation of the market of virtual assets in accordance with modern Ukrainian realities are determined. Conclusions. The difference between national laws in the field of regulation of virtual assets is proved. It is argued that the main vector of regulation is aimed at strengthening control over the transparency and accountability of transactions with virtual assets, cybersecurity and mandatory user verification. The main directions of increasing the settlement and trust in virtual assets are formulated: production of standards and rules of cryptocurrency circulation, in order to bring it to the rank of a competitive means of payment; consolidation of the official status of cryptocurrency; formation of an open ecosystem through effective interaction of all participants in the process of buying / selling cryptocurrency; formation of a legal trading platform for cryptocurrency circulation; support of information literacy of the population to understand the benefits and risks of virtual currency etc.